Development of XYZ stage-type display robot system for stock and disposal tasks in convenience stores. (2nd December 2022) - Seki, Masashi; Wada, Kazuyoshi; Kitajima, Yosuke; Hashimoto, Masato; Tomizawa, Tetsuo
ABSTRACT: In recent years, the automation of stocking and disposal operations in convenience stores has attracted great attention. However, these operations have not yet been completely automated. This study describes the development of an XYZ stage-type display robot system that can automatically perform stocking and disposal operations in convenience stores. In the proposed approach, the robot moves along the backyard of the store and performs the stocking and disposal operations from behind the display case. The robot is equipped with an XYZ stage to move the robot hand in three-dimensional space, a stage lifting mechanism to move the XYZ stage vertically, and a shelf drawing mechanism to pull the shelf out. Furthermore, the robot can automatically perform tasks according to the list of operating procedures input in advance. A performance evaluation experiment was conducted using 20 product mock ups of six different types of products available at convenience stores. A robot equipped with 8 new products worked on a display case with 12 products placed randomly. During the operation, robot (I) retrieved the discarded products from the shelf board, (II) placed the new products on the shelf board, and (III) placed the products faceup. The average success rate was 74% and the average time required to complete the operation was 9 min and 54 s. We registered the developed robot with the World Robot Summit 2020 Future Convenience Store Challenge and were ranked the second best. GRAPHICAL ABSTRACT: UF0001